Third-Order Newton-Type Methods Combined with Vector Extrapolation for Solving Nonlinear Systems - Wen Zhou; Jisheng Kou (Abstract and Applied Analysis)
We present a third-order method for solving the systems of nonlinear equations. This method is a Newton-type scheme with the vector extrapolation. We establish the local and semilocal convergence of this method. Numerical results show that the composite method is more robust and efficient than a number of Newton-type methods with the other vector extrapolations.